The role and influence of advertising and public authorities on the health-related behaviours development among lower secondary - Olejniczak, Dominik; Płusa, Aneta; Religioni, Urszula (Polish Journal of Public Health, 2013)
Introduction. Adolescence is the period during which a man shapes his habits, attitudes and health behaviours. This is the time when man searches authorities who can be the role models for young people. According to the definition, authority is a social recognition, prestige of individuals, groups and social institutions based on the reputable values of a given society Aim. The aim of the study was to determine what elements of advertising affect the health behaviours of young people and to what degree. Matherial and methods. The study was conducted among 187 students of lower secondary school, inhabitants of the city of Kielce. The surveyed group consisted of 45 students aged 14, 78 at the age of 15, and 57 at the age of 16. Among lower secondary school students, 48% were girls, while 52% were boys. An anonymous questionnaire was used to achieve the aim of this study. The questionnaire consisted of 19 closed questions. Results. Fifty-six percent of girls and 45% of boys believe that advertising has an impact on people. For the large part of girls (33%) the most important was the musical setting and for 31% of boys, concrete facts and information about the product were essential. What is more, 72% of girls and 50% boys pay attention to the information about famous people presented in the mass media. Disscusion. Sixty percent of respondents believe that stimulants are attractive. Similarly, the research conducted by Borzucka-Sitkiewicz shows that the influence of peers and fashion are the most important factors influencing the decisions to reaching for cigarettes. According to own research, 72% of respondents aged 14-16, draw attention to the information about well-known people placed in the mass media. Similar results are indicated in the study “Stars and rumours”, according to which 86% of respondents confirmed they were interested in this subject. Conclusions. Smoking cigarettes and consumption of alcohol by young people are the components of family, peers and the media influence. In addition, public awareness-raising campaigns related to health topics can have the impact on the lifestyle of young people